Crypto laundering prevention in Indonesia: The role of regulatory technology and financial intelligence unit - Fajri, Kharisma Fatmalina; Urumsah, Dekar (Journal of Accounting and Investment, 2024)
Research aims: In Indonesia, crypto laundering has become an emerging threat through digital payments since 2015. This study aims to elaborate the crypto laundering prevention through the utilization of regulatory technology (RegTech) and the role of the Financial Intelligence Unit (FIU). Design/Methodology/Approach: The study was conducted using a qualitative content analysis approach with the support of NVivo 12. Data was sourced from secondary data in the form of law documents that have been established and published by the Commodity Futures Trading Regulatory Agency (CFTR). Research findings: Crypto laundering prevention is implemented through Know Your Customer (KYC) and transaction monitoring based on a risk-based approach. Normatively, KYC and transaction monitoring should be implemented on RegTech-based face recognition for KYC and blockchain analytic tools for transaction monitoring. Furthermore, the findings revealed that the FIU in Indonesia is the Indonesian Transaction Report and Analysis Center (INTRAC) which has the authority to receive and conduct further analysis of transaction monitoring results. INTRAC conducts advanced analysis with a ‘follow the money’ approach. The existence of INTRAC’s role depends on the tools, technology, and human resources that represent it.Theoretical contribution/Originality: This study contributes to knowledge in the field of forensic accounting. The findings and discussions in this study provide valuable insights into the current contemporary accounting issues and their relationship with other disciplines.Practitioner/Implication: This study provides insights for regulators to collaborate with various experts from information technology and environmental fields regarding developing regulations and policies to prevent crypto laundering. Research limitation: The data used was only sourced from secondary data (regulatory documents), so the role of RegTech and FIU was only studied normatively.